Bimbingan Islami Melalui Mujahadahh Shalawat Ummi Untuk Meningkatkan Religiusitas Masyarakat (Studi Deskriptif Kampung Babakan Jawa RT 01 RW 12 Desa Bojongloa Kecamatan Rancaekek Kabupaten Bandung) - Mustika, Tiara; Satriah, Lilis; Lukman, Dede (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2024)
The purpose of this study is to find out how the program, process and results of Islamic guidance through mujahadah shalawat ummi. This research uses descriptive qualitative method. Data collection techniques used were observation, interviews and questionnaires distributed to 10% of the total population or 95 people out of 950 people. The results of this study are the mujahadah shalawat ummi program which is carried out once a month. The material given is about Aqeedah, Worship and Morals with a series of sunnah worship and closed with a prayer. The increasing religiosity of the community can be seen from several aspects, namely aspects of strong faith, having high worship values, having good morals, and fourth, having a basic understanding of religion.